2011
DOI: 10.1007/s10965-011-9595-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chain flexibility in the network structure on the viscoelasticity of epoxy thermosets

Abstract: In this paper a detailed study in investigating the effect of the chain flexibility in epoxy-amine crosslinked network is done. In order to introduce flexibility into the crosslinked network a homologous series of four aliphatic diamine curing agents varying only in the chain length and having a constant functionality (f=4) is taken and cured stoichiometrically with aromatic epoxy (f=2) resin. For each of the cured mixture the viscoelastic master curve and corresponding shift factors were determined. It is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 19 publications
2
36
0
1
Order By: Relevance
“…Nowadays, new technical developments create a demand for new materials, one of the examples is using liquid crystalline epoxy resins to produce polymer networks [1][2][3][4][5][6][7][8][9][10]. On the other hand, recent research has shown that properties of epoxy polymers can be improved by addition of some inorganic materials as fillers [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, new technical developments create a demand for new materials, one of the examples is using liquid crystalline epoxy resins to produce polymer networks [1][2][3][4][5][6][7][8][9][10]. On the other hand, recent research has shown that properties of epoxy polymers can be improved by addition of some inorganic materials as fillers [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The storage modulus data generated a unique master curve using the shift factors. Initially, the storage modulus master curves were modeled using Hivrialiak Negami (HN) fit function 11, 28. Also, mathematical model such as generalized Maxwell model can also be used to describe the storage modulus master curves 29.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work,10, 11 model systems are selected based on epoxy‐amine reactants. In the first model system10 the average functionality of the epoxy (Bisphenol A diglycidyl ether; BADGE) resin is f E = 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample heating/Cooling rate of 5°C/min was used to determine the thermal expansion coefficient along with the Tg values between the temperature interval of 30°C-120°C. Coefficient of linear thermal expansion was calculated above and below the Tg along with the entire temperature interval The coefficient of thermal expansion (α) is determined using the equation [19].…”
Section: Thermo Mechanical Analysismentioning
confidence: 99%